2021
DOI: 10.1111/jnc.15436
|View full text |Cite
|
Sign up to set email alerts
|

The adenosine A2Areceptor alleviates postoperative delirium‐like behaviors by restoring blood cerebrospinal barrier permeability in rats

Abstract: Postoperative delirium (POD) is a common post‐operative complication in elderly patients that is associated with increased morbidity and mortality. However, the neuropathogenesis of this complication remains unknown. The blood–cerebrospinal fluid barrier (BCB) and brain–blood barrier (BBB) are composed of tight junctions between cells that form physical barriers, and BBB damage plays an important role in the neuropathogenesis of POD. Nevertheless, the role of BCB in POD remains to be elucidated. Herein, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…Studies are underway to evaluate BBB dysfunction as a risk factor for postoperative delirium. Several animal models have reported that anesthesia/surgery can decrease the levels of TJ proteins, and increase the leakage of BBB or blood-cerebrospinal barrier (BCB) accompanied by delirium-like behavior ( Yang et al, 2017 ; Wen et al, 2020 ; Chen et al, 2021 ; Li et al, 2021 ). The present study reconfirmed that BBB disruption was associated with anesthesia/surgery-induced delirium-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Studies are underway to evaluate BBB dysfunction as a risk factor for postoperative delirium. Several animal models have reported that anesthesia/surgery can decrease the levels of TJ proteins, and increase the leakage of BBB or blood-cerebrospinal barrier (BCB) accompanied by delirium-like behavior ( Yang et al, 2017 ; Wen et al, 2020 ; Chen et al, 2021 ; Li et al, 2021 ). The present study reconfirmed that BBB disruption was associated with anesthesia/surgery-induced delirium-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is still uncertain whether POD and dNCR are distinct pathologies or "two sides of the same coin" (Olotu, 2020), mainly because of the lack of animal models of POD. Peng et al used 4-month-old mice to determine the effects of anesthesia/surgery on natural and learned behaviors, and the results suggested that this mouse model could exhibit acute onset and a fluctuating course of behaviors similar to POD (Peng et al, 2016;Chen et al, 2021). Illendula et al used 18to 20-month-old mice to examine anesthesia, surgery, and the intensive care unit environment and found that these insults impaired mouse behaviors that depend on attention, memory, and thought organization.…”
Section: Discussionmentioning
confidence: 99%
“…The OFT was used to evaluate locomotion and anxiety-like behavior of the rodents [ 5 , 10 ]. The open field chamber was placed in a quiet and dim environment, and mice were placed in the center of chamber and allowed to explore freely for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Adenosine is an endogenous purine nucleoside that regulates numerous physiological functions by activating the four G protein-coupled receptors A 1 , A 2A , A 2B and A 3 [ 9 , 10 ]. CD73 (ecto-5-nucleoditase) plays an important role in the immune inflammatory response against various diseases.…”
Section: Introductionmentioning
confidence: 99%